Pyroaerobiology: the aerosolization and transport of viable microbial life by wildland fire. Issue 11 (15th November 2018) - Kobziar, Leda N.; Pingree, Melissa R. A.; Larson, Heather; Dreaden, Tyler J.; Green, Shelby; Smith, Jason A.
Abstract: The field of aerobiology is expanding due to a recognition of the diversity of roles microbes play in both terrestrial and atmospheric ecology. Smoke from global biomass burning has had significant and widespread ecological and human health consequences, but the living component of smoke has received little attention. Microbes aerosolized and transported by wildland fire may have profound effects on atmospheric and environmental factors, acting as nuclei for ice condensation, transporting pathogens or symbionts, and otherwise influencing ecosystems and human populations downwind. The potential for smoke to aerosolize and transport viable microbes is a virtually blank piece of the microbial biogeography puzzle with far‐reaching implications. This study characterized the aerosolization of viable microbes via wildland fire smoke from burns in contrasting coniferous forests. Seventy aerosolized microbial morphotypes were recovered, and of these, a subset was identified using DNA analysis which revealed both pathogenic and non‐pathogenic fungal species. Overall microbial colony‐forming units decreased with increasing distance from smoke source, driven by bacterial abundance. Organisms were more abundant in smoke derived from mechanically treated fuels than intact forest floors and were most abundant in smoke from a dry, biennially burned Pinus palustris sandhill forest in Florida. Our findings of smoke‐transported viable microbes have implications for ecosystem restoration/conservation, global biodiversity, meteorology, and human health.